2004
DOI: 10.1111/j.1468-2982.2003.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prophylactic Effect of Valproate on Glyceryltrinitrate induced Migraine

Abstract: In this study the human glyceryltrinitrate (GTN) model of migraine was for the first time used to test the effect of a prophylactic drug. We chose to test valproate due to its well documented effect as a migraine prophylactic drug. Efficacy of this compound would support the usefulness of the model in prophylactic antimigraine drug development. Twelve patients with migraine without aura were included in a randomized double blind crossover study. Valproate 1000 mg or placebo was given daily, each for a minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 20 publications
(22 reference statements)
1
34
0
Order By: Relevance
“…This could limit the use of the model. In a recent study with the same study design, we found that sodium valproate could prevent GTN‐induced headache/migraine in migraine patients (8). The present study may therefore indicate that propranolol has a different mechanism of action in preventing migraine and that this effect is overruled or bypassed by the nitric oxide (NO) donor GTN.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This could limit the use of the model. In a recent study with the same study design, we found that sodium valproate could prevent GTN‐induced headache/migraine in migraine patients (8). The present study may therefore indicate that propranolol has a different mechanism of action in preventing migraine and that this effect is overruled or bypassed by the nitric oxide (NO) donor GTN.…”
Section: Discussionmentioning
confidence: 87%
“…The prophylactic effect of propranolol and other β‐adrenoceptor antagonists (β‐blockers) in migraine is well established (7). We have previously shown the efficacy of sodium valproate in preventing GTN‐induced headache and migraine (8). We therefore studied the effect of propranolol prophylaxis on GTN‐induced headache and migraine, in order to validate our model further.…”
Section: Introductionmentioning
confidence: 99%
“…However, 30 min to 4 h after administration of NTG, patients with a history of migraine also report the onset of delayed headache symptoms that are indistinguishable from their environmentally triggered migraines (7). Furthermore, experimentally administered NTG induces migrainous headaches that are accompanied by thermal allodynia (8), activate brainstem regions that are also active in a migraine attack (9) and can be blocked by migraine prophylactic agents (10,11). NTG can even trigger aura in some patients with an established history of migraine with aura (12).…”
Section: Introductionmentioning
confidence: 99%
“…Human models of migraine have been developed to study drug effects under standardised conditions. The glyceryl trinitrate (GTN) model, which uses systemic or sublingual administration of GTN, is the most commonly used to induce neurovascular headaches (cluster headache and migraine) and is considered as safe, reproducible and reliable 10–15 . Sublingual administration of GTN is easier and this modality has been shown to reproduce the main features of spontaneous headache attacks experienced by patients with migraine without aura and cluster headaches 13 .…”
Section: Introductionmentioning
confidence: 99%